BUAH NAGA SEBAGAI SUMBER PENDAPATAN ALTERNATIF PETANI KELAPA DI KECAMATAN TOBELO TIMUR - Zeth Patty; Ariance Y. Kastanja; Nonice Manikome (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
Low selling prices, low coconut production due to old age of coconut plants, and monoculture planting patterns are some of the factors that cause low income of coconut farmers so they live in poverty. Service activities carried out on coconut farmers in East Tobelo Sub district with the aim of training farmers to have the knowledge and skills to cultivate dragon fruit plants as intercrops among coconut plants. Problems faced by farmers include, lack of knowledge and skills in cultivating dragon fruit plants. The target to be achieved is the increasing knowledge and skills of coconut farmers in dragon fruit cultivation techniques. The methods used include counseling, training and planting dragon fruits in demonstration plot. This service program can be concluded to be able to produce expected outcomes including providing new knowledge and skills for group members while at the same time encouraging the community to seek additional income independently